(untitled) (Proceedings of the International Conference on Public Health, 2025)
The advocacy to increase skilled care services uptake for pregnant women has become part of the fight against reducing maternal mortality, particularly in developing countries. Using traditional birth attendants, this approach has initiated formal training sessions aimed at changing their mindsets and increasing accessibility of maternity services for all women in communities through this strategy. Therefore, the aim of this study is to identify gaps that exist within the formal training programmes conducted in Nigeria to understand approaches that can further assist in integrating TBAs into the healthcare system. Using a scoping review approach, a protocol was developed from the Arksey and O’Malley framework and Joan Briggs Institute guidelines for a detailed search strategy. 5 databases were searched including, CINAHL, MEDLINE, PubMed, Scopus, Web of Science and Psyche App. 16 articles were identified, which met the inclusion criteria developed. Data was analysed using thematic analysis through continuously mapping and reviewing of information to develop 4 themes. These are HIV coverage programmes to improve MTCT, Postnatal referral practices, Immunisation strategy uptake and Infection control practices. The findings suggest that implemented strategies and policies on formal training are not generalized despite evidence of training conducted across several regions. Furthermore, methods of post-training assessment are not equal due to independent agencies having control over training sessions. Moreover, community-based level research was mostly conducted while assessing the overall impact of the intervention rather than specific to TBAs opinions. Therefore, future recommendations are to focus on understanding TBAs perceptions towards sustainability of the training programmes and increasing skilled care services for all women.